Presence of Foraminifera of Superfamily Komokioidea (Order Astrorhizida) in Colombian deep Caribbean waters - Tavera-Martínez, Laura; Marchant, Margarita (Zootaxa, 2017)
Research regarding deep-sea benthic foraminifera in the Colombian Caribbean requires further development given the complete lack of information related to the different groups that constitute associations and the ecological functions they fulfill. For this purpose, a taxonomic description of Superfamily Komokioidea was composed from macrofauna samples from between 1,215 m and 3,179 m depth, obtained during the research cruise ANH-COL 4 and COL 5 carried out in 2014. Results showed foraminifera belonging to the three families: Komokiidae, Baculellidae, and Normaninidae, inclu-ding five genera (Lana, Komokia, Ipoa, Normaninam, and Catena) and five species (Lana neglecta, Komokia multiramosa, Normanina conferta, Ipoa fragila, and Catena piriformis). This study presents knowledge regarding deep-sea Colombian Caribbean benthic foraminifera, which to date have not been recorded from this region. Their depth distribution when compared with other studies from the Atlantic and Pacific, allows the expansion of taxonomic inventories and the characterization of biodiversity within poorly explored regions.